Overcoming the endodormancy of apple trees in Southern Brazil - Schlemper C.* (2010)
Apple trees (Malus × domestica Borkh) planted in the warm regions do not completely emerge from endodormancy. This results in trees exhibiting reduction and irregularity in the opened flower and vegetative buds. The use of chemical treatments to overcome the endodormancy induces and standardizes bud break. The goal of the present study was to evaluate the effect of different chemical products on overcoming the endodormancy of 'Fuji Suprema' and 'Gala Galaxy' apples. The experiment was conducted at the Frutirol orchards in the city of Vacaria, Rio Grande do Sul State (28°29'27,12" S and 50°56'09,78" W). The treatments included Erger® (inorganic hydrogen compound) 4% + potassium nitrate 5%; Acordex® 1.5% (Zn - 8%, S - 3.8%, Mo - 0.15%, Co - 0.15%) + Kymon Plus® 0,2% (N - 9%, K - 3%, aminoacids) + mineral oil 3%; Dormex® (Hydrogen Cyanamide H2CN2) 0.7% + mineral oil 3%; Dormex® 0.1% + mineral oil 3%; mineral oil 5%; and a control which was treated only with water. The application of the treatments and the first bud count was done on 05/09/2007, the others assessments were made in 21/09, 05/10 and 30/10/2007 to determine the rate of bud break. The number of fruits was counted on 09/01/2008. The qualities of fruits were assessed by measuring total soluble solids, acidity, pH, weight of fruits and flesh firmness. The experimental design was conducted in a randomized block design, with three blocks and 10 plants of each cultivar per plot. The treatment Dormex® 0.7% + mineral oil 3% obtained the best result for bud break, weight of fruits and showed greater uniformity in the production in both cultivars, but with lower yield than the control. The control showed greater firmness of flesh, acidity and total soluble solids. Treatments did not affect pH.